Xylopia parviflora (A. Rich.) Benth. Ameliorates Ketamine-Induced Positive, Negative, and Cognitive Symptoms of Psychosis through Down-regulation of Neuro-oxidative Damage in Mice (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Ethno-botanical investigations on Xylopia parviflora (A. Rich.) Benth. revealed its application in the management of neurological disorders, including psychotic conditions.Objective: To evaluate the neuroprotective effects of the hydroethanol leaf extract of Xylopia parviflora (XPE) on the positive, negative, and cognitive manifestations of psychosis in mouse models. .Methods: Thirty mice were allocated into six groups (n=5). Treatments for each group are as follows: distilled water only (10 mL/kg; Grp A), distilled water + ketamine (50 mg/kg; Grp B), the extract (50, 100, and 200 mg/kg; Grps C-E), and haloperidol (5 mg/kg; Grp F). One hour subsequent to the administration of the extract and haloperidol, all groups were administered ketamine (50 mg/kg, i.p.) to induce psychosis. These treatment regimens were repeated over a period of 21 consecutive days. Twenty-four hours following the final treatment, the mice underwent forced swim (FST), open field (OFT), and object recognition tests (ORT), during which relevant parameters were monitored for a duration of five minutes. Thereafter, the animals were euthanized via cervical dislocation, and their brain tissues were harvested for antioxidant analyses.Results: XPE (50-200 mg/kg) diminished the duration of immobility in the FST; enhanced the duration spent with the novel object and reduced the duration spent with the familiar object in the ORT; and diminished the frequency of section crossings in the OFT when compared with the distilled water + ketamine treated group. Furthermore, XPE increased antioxidant biomarkers in the brain.Conclusion: XPE ameliorates ketamine-induced symptoms of psychosis through the attenuation of oxidative stress.
Keywords: Xylopia parviflora; Ketamine; Psychosis; Antipsychotic; Ethno-botanical